Research on Windage Power Loss of High-speed Arc Tooth Cylindrical Gear - Shuai Mo; Heyu Dang; Zhenxing Zou; Wenjie Tang; Zongxiang Yue; Hanjun Gao (Jixie chuandong)
For gears running at high speeds， windage power loss is one of the main factors for low transmission efficiency. Computational fluid dynamics（CFD） technology is used to establish the air flow field model around the arc tooth cylindrical gear. The digital twin simulation calculation is performed to obtain the velocity vector diagram and windage loss power of the air flow around the arc tooth cylindrical gear. The results show that the baffle around the arc tooth cylindrical gear can effectively reduce windage power loss， the smaller the axial baffle spacing，the smaller the windage power loss of the arc tooth cylindrical gear. When the axial baffle gap is 2 mm，the windage power loss is reduced by 27.80% compared with the axial baffle gap of 10 mm. But for the radial baffle，it is not that the smaller the gap， the smaller the windage power loss of the arc tooth cylindrical gear. Different types of tooth shapes have different windage power losses under the same conditions. Under the same conditions， it is found that the spur gear with a pressure angle of 25° reduces the windage power loss by 23.84% compared with the standard helical gear.